Níveis de concentrado na dieta de bovinos - Missio, Regis Luis (2007)
The study was developed to evaluate the effect of the increment of concentrate in beef cattle diet, slaughtered with 14-16 months of age, on animal performance, economic evaluation, ingestive behavior and quantitative and qualitative characteristics of carcass and meat. Sixteen, not castrated Charolais-Nellore crossbred, steers were used and fed with 22, 40, 59 or 79% of concentrate in the diet (LC). The animals were randomly distributed and each treatment contained four. The average initial age and weight were of 9.32 months and 192.44 kg, respectively. The animals were feedlot fineshed until they reached 400 kg of body weight. The supplied diet was isoproteic and the used forage was the corn silage. The finals age and weight, neutral fiber detergent intake, feed conversion, month profit, feeding and rumination times, number of rumination bolus, neutral detergent fiber rumination efficiency and physiologic maturity decreased linearly with increase of concentrate in the diet. The dry matter intake in percentage of live weight and metabolic size presented a quadratic behavior, increasing until 67% of concentrate in diet. The digestible energy intake, average daily weight gain, idle time, dry matter feeding and rumination efficiencies, sawcut percentage, meat color and texture presented a linear increase with the increment of the concentrate level in diet. Beef cattle finishing of not castrated steers between 14-16 months of age and feedlot with final weight of 190 kg is economically feasible using a concentrate increment between 26 and 61% in diet. The major concentrate supply in diet increases the feeding and rumination efficiencies and improves meat visual aspect.